MODEL OF EXERCISE IMAGERY FOR SUPPORTS THE SUCCESS OF KICK, BEARING AND SCISSOR TECHNIQUES - Bayu Iswana (Universitas Negeri Gorontalo, 2019)
This study aims to create an imagery training model as a form of psychic exercise that supports the success of kicking, slamming and cutting techniques. This research uses research and development methods (Research and Development). The subject of this study is the martial arts athlete who won the South Sumatra Porprov 2017 championship, which is the product of this training model is feasible and declared effective and efficient through several trials. Then the model can be applied to the training process. Furthermore, researchers collaborate with competent parties in making mass products in the form of books and CDs. The results of the study were Specific Cognitive, Motivational Specific, Motivational General Arousal, Motivational General Mastery, then the four training models were tested by expert validation on the draft that had been carried out on a large scale expert assessment of the four above 80%. So the researchers concluded that the product model of this exercise could be used as an imagery exercise as a model of imagery training as a form of psychic exercise that supports the success of kick, kick and cut techniques.